Enhancing Maritime Vocational Education: A Qualitative Analysis of Curriculum Alignment, Technological Integration, and Sustainability Practices - Marihot Simanjuntak; Susi Herawati; Imam Fahcruddin; April Gunawan Malau (Dinasti International Journal of Education Management and Social Science, 2026)
Despite growing global recognition of the need to modernise maritime vocational education, there remains a significant research gap in understanding how curriculum, technological integration, and sustainability practices align with current industry demands in developing countries, particularly in Indonesian maritime institutions. This study addresses this gap by exploring the experiences and perceptions of three key stakeholder groups—maritime industry professionals (n = 5), lecturers (n = 5), and recent graduates (n = 5)—totalling 15 informants selected through purposive sampling. Using Braun and Clarke's (2006) six-phase thematic analysis, three major themes emerged: (1) partial curriculum–industry alignment, with curricula rooted in conventional seafaring competencies yet inadequately responsive to digital and autonomous shipping innovations; (2) a substantial technology integration deficit, whereby exposure to advanced digital systems such as electronic chart display and information systems (ECDIS) and integrated bridge systems remains superficial; and (3) a sustainability education gap, in which environmental and decarbonisation literacy is introduced theoretically but lacks applied, IMO-aligned practical training. These findings suggest the need for structured curriculum reform, industry co-design mechanisms, and investment in simulation-based and green-technology training infrastructure. This study contributes to the emerging literature on maritime education reform and offers actionable implications for institutions, policymakers, and the broader maritime training community.